Perancangan Sistem Informasi Persediaan Obat Pada Apotek Asima - Silalahi, Calvin Matius; Hutapea, Marlyna I.; Siringoringo, Rimbun (Universitas Methodist Indonesia, 2024)
The design of the Drug Inventory Information System at Asima Pharmacy aims to improve efficiency and accuracy in managing drug stock. This system is designed to facilitate drug data management, real-time stock monitoring, and fast and accurate reporting. This study uses a software development methodology that includes needs analysis, system design, implementation, and testing. The results of this study are a web-based information system that allows pharmacy managers to access inventory data easily and quickly, reduce the risk of shortages or excess stock, and speed up the drug reporting process. This system is expected to improve the quality of service at Asima Pharmacy by providing accurate and up-to-date information on drug inventory.